Effect of skills and work safety on the craftsman productivity In The Sentra Pandai Besi Teratak Rumbio Jaya - Zakiyul Kamal; Librina Tria Putri; Mustafa Kamal (STIE Bangkinang Publishing, 2022)
This study aims to determine the effect of skills and work safety on the productivity of craftsmen at Sentra Pandai Besi Teratak Rumbio Jaya. The analysis used in this research is multiple linear analysis. The population in this study were all machete craftsmen who were members of the Rumbio Jaya Teratak Blacksmith Center, amounting to 62 people. While the sample is taken from the entire population as a sample using the census method or total sampling, which is a sampling technique when all members of the population are used as samples (Sugiyono, 2017:67). Hypothesis testing is done by testing simultaneously and partially testing. Based on the results of the study, it can be concluded that simultaneously and partially skills and work safety affect the productivity of craftsmen at Sentra Pandai Besi Teratak Rumbio Jaya. The contribution of the craftsman's productivity variable is 53,9% determined by skills and work safety while the remaining 46,1% is determined by other variables outside of this study.